Systemic and local decorin levels mirror the clinical course of pancreatic cancer - Svensson, Maja; Lehn, Sophie; Jacobsen, Hedda; Olsson Hau, Sofie ; 0000-0002-1702-9884; Jönsson, Göran; Pietras, Kristian ; 0000-0001-6738-4705; Jirström, Karin ; 0000-0003-2257-5000 (The Journal of Pathology: Clinical Research, 2026)
Despite significant progress in oncology research, pancreatic cancer remains inherently difficult to treat, and the mechanisms underlying therapeutic resistance remain unresolved. Decorin (DCN), a member of the family of small leucine-rich proteoglycans, has emerged as a versatile actor in various malignant diseases. The aim of this study was to further explore the potential clinical significance of DCN in pancreatic cancer, both regarding its dynamics in serum during chemotherapy and its compartmental and cellular distribution in tumour tissue. To this end, repeated on-treatment levels of soluble DCN were measured using proximity extension assay in 124 patients enrolled in a prospective, observational clinical study, inviting patients diagnosed with pancreatic or other pancreatobiliary-type periampullary adenocarcinoma eligible for adjuvant (n = 30) or first-line palliative (n = 94) chemotherapy. Multiplexed immunofluorescence was applied to map DCN and the associated immune landscape in resected tumours. The results showed increasing levels of DCN in serum after initiation of chemotherapy in palliative, but not in adjuvant, patients. A higher rate of change of serum DCN was an independent adverse prognostic factor in both treatment settings. There was no significant association between systemic levels and local DCN expression. Varying expression of DCN was denoted in both tumour cells, immune cells and stroma, but the prognostic significance was mainly assigned to its expression in B cells. In particular, a higher percentage of DCN positive B cells, overall and in interaction with tumour cells, were independent predictors of shorter survival. In summary, this study is the first to demonstrate the potential clinical utility of on-treatment monitoring of systemic DCN in patients with pancreatic cancer. The findings also provide interesting leads for further research into how DCN may interact with the immune microenvironment to promote tumour development and the emergence of chemoresistance.
© 2025 The Author(s). The Journal of Pathology: Clinical Research published by The Pathological Society of Great Britain and Ireland and John Wiley & Sons Ltd.
Keywords: Humans; Decorin/blood; Pancreatic Neoplasms/pathology; Female; Male; Middle Aged; Aged; Prospective Studies; Biomarkers, Tumor/blood; Tumor Microenvironment; Adenocarcinoma/pathology; Chemotherapy, Adjuvant; Palliative Care; Adult; Aged, 80 and over